Communication of Bichromophore Emission upon Aggregation – Aroyl‐S, N‐ketene Acetals as Multifunctional Sensor Merocyanines. Issue 53 (1st August 2021) - Biesen, Lukas; May, Lars; Nirmalananthan‐Budau, Nithiya; Hoffmann, Katrin; Resch‐Genger, Ute; Müller, Thomas J. J.
Abstract: Aroyl‐ S, N ‐ketene acetal‐based bichromophores can be readily synthesized in a consecutive three‐component synthesis in good to excellent yields by condensation of aroyl chlorides and an N ‐( p ‐bromobenzyl) 2‐methyl benzothiazolium salt followed by a Suzuki coupling, yielding a library of 31 bichromophoric fluorophores with substitution pattern‐tunable emission properties. Varying both chromophores enables different communication pathways between the chromophores, exploiting aggregation‐induced emission (AIE) and energy transfer (ET) properties, and thus, furnishing aggregation‐based fluorescence switches. Possible applications range from fluorometric analysis of alcoholic beverages to pH sensors. Abstract : Multifunctional shining tool : A library of 31 aroyl‐ S, N ‐ketene acetal solid‐state emissive bichromophores, synthesized by a consecutive three‐component reaction (3CR), exhibits aggregation induced emission (AIE), acidochromicity, as well as dual emission and energy transfer in aggregates suitable for alcoholic beverage analysis and encapsulation in micrometer sized polystyrene particles with enhanced fluorescence quantum yield.